CD49b Targeting Inhibits Tumor Growth and Boosts Anti-tumor Immunity - Contreras-Kallens, Pamina; Gálvez-Jirón, Felipe; De Solminihac, Javiera; Elhusseiny, Ahmed; González-Arriagada, Wilfredo A.; Alcayaga-Miranda, Francisca; Noelle, Randolph J.; Pino-Lagos, Karina (Frontiers in Oncology, 2022)
The suppressive function of T-regulatory cells (Tregs) can have a detrimental effect on immune responses against tumor cells. Within the Treg cells subset, a new non-classical population has been reported, which expresses high levels of CD49b molecule and, depending on their activation status, can also express the canonical Tregs transcription factor Foxp3. In this report, we sought to characterize Tregs subsets in a murine melanoma model and disrupt the CD49b/CD29 axis by administering an anti-CD29 antibody in tumor-bearing mice. Our data shows that whereas in the draining lymph nodes, the Tr1 cells subset composes <5% of CD4+ T cells, in the tumor, they reach ∼30% of CD4+ T cells. Furthermore, Tr1 cells share the expression of suppressive molecules, such as Nrp-1, PD-1, and CD73, which are highly expressed on Tr1 cells found in tumor-infiltrating leukocytes (TILs). Regardless of the phenotypic similarities with cTreg cells, Tr1 cells display a low proliferative activity, as shown in the kinetics and the incorporation of 5-bromodeoxyuridine (BrdU) experiments. With the intent to impact on Tr1 cells, we administered anti-CD29 antibody into tumor mice, observing that the treatment effectively inhibits tumor growth. This effect is at least mediated by the enrichment of pro-inflammatory T cells, including IFN-γ+ cTreg and IFN-γ+ Tr1 cells (with reduced expression of IL-10), plus Th1 and Tc cells. In this study, we present Tr1 cell characterization in tumor-bearing animals and introduce CD29 as a target for tumor therapy, supported by a meta-analysis indicating that CD29 is present in human biopsies.